Customer awareness and cyber security in the Organisation for Economic Co-operation and Development countries - Aws AlHares (17541741) (2024)
In certain circumstances, millions of documents have been exposed due to an increase in the yearly incidence of cyber security breaches in recent years. In the context of the banking industry’s digital transition in the Organisation for Economic Co-operation and Development (OECD), this study investigates consumer knowledge of and satisfaction with cyber security. The study is empirical and based on the data obtained from 240 banking clients in OECD. Cyber attacks, phishing, and hacking have been examined from diverse angles. The effects of cyber attacks, phishing, hacking, cyber security help, and expectations on cyber security’s technical awareness are investigated using analysis of variance (ANOVA) and bivariate regression analysis. The findings demonstrate how the banking industry has benefited from digital change, and users gain from online services. Nonetheless, a customer’s degree of awareness regarding hacking, phishing, and cyber attacks will have an impact on how satisfied they are with digital transactions. The findings also showed that banks should regularly offer training programs to protect their clients from cyber attacks and that customers need more assurance from banks about security-related issues. Banks might easily meet their long-term sustainability goals if they implemented better safer cyber security management. This paper has repercussions for policymakers, investors, and business organizations. Importantly, our study reveals how customer awareness and cyber security are related in OECD. Other Information Published in: Corporate and Business Strategy Review License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.22495/cbsrv5i1siart11